Gender imbalance in executive management positions at the Mexican National Institutes of Health - Lucero Soledad Rivera-Romano; Cristobal Fresno; Enrique Hernández-Lemus; Mireya Martínez-García; Maite Vallejo (BMC, 2020)
Abstract Background Around the world, there is a significant difference in the proportion of women with access to leadership in healthcare with respect to men. This article studies gender imbalance and wage gap in managerial, executive, and directive job positions at the Mexican National Institutes of Health. Methods Cohort data were described using a visual circular representation and modeled using a generalized linear model. Analysis of variance was used to assess model significance, and posterior Fisher's least significant differences were analyzed when appropriate. Results This study demonstrated that there is a gender imbalance distribution among the hierarchical position at the Mexican National Health Institutes and also exposed that the wage gap exists mainly in the (highest or lowest) ranks in hierarchical order. Conclusions Since the majority of the healthcare workforce is female, Mexican women are still underrepresented in executive and directive management positions at national healthcare organizations.